The Effect of Organizational Intelligence on Workforce Agility with Psychological Empowerment as a Mediating Variable on Employees of PT. X Medan - Larasati, Shafisiyah Adya; Hardjo, Suryani; Aisyah, Siti (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Organizations need employees who are able to proactively and adaptively improve, learn, and solve problems from their daily work.Workforce agilitycan help organizations with the agility of their workforce in facing changes, companies or organizations need to have agile members/personnel to form a team that has work agility. The above problems need to be developed throughorganizational intelligence(OI) is the ability to mobilize an organization to move in accordance with the desired development direction. The purpose of the research is to examine the influenceorganizational intelligencetoworkforce agilitywithpsychological empowermentas a mediating variable. The sampling technique used ispurposive sampling. The results of the study showed that there was an influenceorganizational intelligencetopsychological empowerment, with a CR value (t-count) of 5.223 > 1.96 and/or P-value with a *** sign (very significant) 0.000 < 0.05. There is an influencepsychological empowermenttoworkforce agilitywith a CR value (t-count) of 9.472 > 1.96 and a P-value with the *** sign (very significant) 0.000 < 0.05. There is an influenceorganizational intelligencetoworkforce agilitywith a CR value (t-count) of 6.057 > 1.96 or a P-value with the *** sign (very significant) 0.000 < 0.05. There is an influenceorganizational intelligencetoworkforce agilitywithpsychological empowermentas a mediating variable with the Sobel test calculation it is known that the Two-tailed P-value (significance) is 0.000 < 0.05 or the Sobel test statistic value is 4.578 > 1.96.